From National to Local (and Back). Religious Freedom and the Right to the City in Italy - Bossi, Luca; Ricucci, Roberta (Italian Sociological Review, 2023)
Urban space can be seen as the social field in which the religious diversification of European societies emerges and assumes visibility. In this contexts, minority places of worship can be used at the same time as the marker of the presence – past and/or present – of a specific religious group and a reliable marker of religious diversity, helping assess the state of health of religious pluralism in itself. More than the national level of State-religions relationships, the local milieu of the city contributes in shaping and assessing contemporary forms of religious life. At the same time, cities represent the arena where old and new minorities struggle for space, visibility and recognition. At this level, the right to religious freedom interacts with the right to the city: local public institutions increasingly stand at the forefront in the regulation of religion-driven needs. This contribution presents evidences from research conducted in the city of Turin, a representative case in the Italian scenario on the above-mentioned issues. Based on a comparative case study, it focuses on the different dynamics of symbolical positioning and material placing enacted by four different minorities: Islam, Judaism, Orthodoxy, and Scientology. Drawing on empirical evidences collected over a period of three years, we analyse the actor constellation involved in the regulation of religious diversity in the city, discussing both policy implications and policy transferability guidelines.